Integration of Geogebra Software Into Mathematics Instruction - Olajumoke Olayemi Salami; Erica Dorethea Spangenberg (Studies in Learning and Teaching, 2024)
The study focused on how learners' performance and attitudes in mathematics were affected by the GeoGebra software. Among the most significant obstacles facing the teaching and learning of mathematics has been the need for instructional tools, particularly those incorporating information and communication technology (ICT). The design of the study was quasi-experimental with a sample size of 80 respondents selected from the population of the study with the use of a purposive sampling technique. The selection of the schools was based on the availability of working computer systems. Using basic random sampling, two intact classes were divided into experimental and control groups. The findings of the Student Achievement Test in Mathematics, SATM, indicated that pupils who had been taught GeoGebra performed significantly better at the post-test level than the pre-test level (t = 2.14; p > 0.05). The results of the Mathematics Attitudinal Scale (MAS) also demonstrated that students' attitudes toward mathematics were highly correlated with their proficiency with GeoGebra (t =2.11; p > 0.05). The investigation concluded that there are insufficient teaching materials available for mathematics training. Thus, integrating GeoGebra software into the teaching of mathematics significantly improves secondary school students' performance in mathematics.